Managing operational risks in small and medium manufacturing enterprises - a strategic approach - Islam, Ariful (Henry Stewart Talks, 2011)
Risks in general, Operational disturbances, Causes and consequences of disturbances (short term and long term effects), Operational risks associated with disturbances -Typical internal and external disturbances, and their root causes (risk determinants), Managerial approach to deal with these risks, Strategic approach and framework for SMEs to deal with operational risks